Organizational Commitment Model by Explaining the Role of Organizational Innovation, Organizational Culture and Creating Shared Value - Amir Mohammad Colabi (پژوهش‌های مدیریت عمومی, 2022)
Abstract Progress and success belong to organizations that equip their human resources with innovation, skills and entrepreneurship by creating the necessary conditions. Using these valuable capabilities, organizations direct other organizational resources to create new values in line with the needs of society. To achieve this, it will be important to attract and retain skilled and quality employee. Maintaining and building commitment in organizations is through the lens of organizational dynamism and innovation so that employees feel engagement and apply their skills; The present study aims to assess the role of creating shared value on organizational commitment and examine the position of corporate social responsibility, organizational culture and organizational innovation on creating organizational commitment. In addition, the role of organizational culture in the relationship between organizational innovation and organizational commitment has been examined. The present study is applied in terms of purpose and descriptive correlational in terms of data collection and analysis. Its statistical population consists of government managers of government organizations in Tehran province. Among them, 357 people were selected by available sampling method as a statistical sample. SPSS and Smart PLS software, in the form of Structural Equation Modeling (SEM), were used to analyze the research data. Creating shared value and organizational innovation is directly related to organizational commitment. Corporate social responsibility also directly and indirectly improves organizational commitment. Organizational culture also moderates the relationship between organizational innovation and organizational commitment. Introduction Competition has increased in all contexts of the organization. To succeed in such an environment, the organization must hire the best workforce and keep them satisfied and committed to the organization. The success of government agencies depends on the ability of managers who are committed to creating value and employing committed human resources. Creating organizational commitment, which is considered as the desire to try and stay in the organization, is one of the issues that have been considered by managers of organizations (Kaplan & Kaplan, 2018:47). Organizational commitment determines how dependent employees are on the organization, how involved they are in the organization, and whether they are prepared to leave the organization (Gopinat, 2020:1859). Commitment activities of employees are very important in building trust and positive behaviors; Because it makes employees feel part of the organization they work for. In most organizations, employee commitment depends on the amount of shared value created. Paying attention to community issues and trying to solve problems leads to increasing employee trust and creating organizational commitment (George & Edward, 2020:256). Creating shared value is a kind of social goodwill for both society and employees, which will lead to organizational commitment by implementing social responsibility; Therefore, the majority of employees should be aware of the company's social responsibility to create the necessary motivation to create shared value in the organization (Amarsaikhan, 2014). An organization that fails to retain its skilled manpower will soon be defeated by other organizations that have the power to employ organizational innovation and have committed employees (Lambert and Hogan, 2010:162). In government organizations, employees have higher expectations of financial resources and fair behavior that organizational culture can provide. This study seeks to examine all these variables in one model; Therefore, the main purpose of this study is to provide an answer to the question of whether the creation of shared value is effective in promoting organizational commitment? How will corporate social responsibility and organizational innovation variables affect this relationship? And can the variable of organizational culture have a moderating role in the relationship between organizational innovation and organizational commitment or not? Methodology The research method is applied in terms of purpose and in terms of collecting descriptive-correlation information (based on structural equation model). To examine the theoretical foundations, the library method was used through authoritative books and articles. The statistical population of the study is government managers in Tehran province. The data collection tool is a questionnaire whose scales were first extracted from theoretical foundations and then designed based on a range of five Likert options. The face validity and content of the questionnaire were reviewed and confirmed by academic experts and the construct validity was confirmed using factor analysis. The average variance extracted index was used to achieve convergent validity. Existence of values higher than 0.5 for the average variance extracted is a necessary condition for convergent validity and a reliability value higher than 0.7 is a necessary condition for appropriate reliability. To analyze the demographic data, SPSS software has been used and to study the research model, structural equation modeling and Smart-PLS have been used. Discussion and Results Today, professionals will be most effective in creating organizational innovation and gaining value for society. These people in government organizations due to low importance to them and low commitment lead to lack of organizational values. One of the features of an organization's superiority over another organization is having a loyal human resource and creating organizational commitment helps managers in progress and success. Organizational commitment is an important factor in the relationship between individuals and the organization; Organizational innovation also plays an important role in improving organizational productivity by creating shared value. Conclusion Given the important role of organizational innovation, providing the desired environment in the organization and providing the necessary training for employees to flourish creativity and create shared value in order to create organizational commitment is essential. Given that organizational structure and organizational culture in some way affect the level of innovation and level of commitment in the organization, so government organizations should gradually move away from mechanical structures to provide a basis for creating shared value and increasing organizational commitment. Managers of the organization should refrain from exercising any direct control and emphasis on the implementation of formal regulations, and by aligning personal and organizational goals to provide the basis for organizational innovation and entrepreneurship.